2021
DOI: 10.1177/2325967120979985
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of Adolescent ACL Reconstruction With Hybrid Hamstring Tendon Autograft-Allograft Versus Hamstring Tendon Autograft Alone

Abstract: Background: Small-diameter semitendinosus-gracilis tendon autografts may be encountered intraoperatively during anterior cruciate ligament reconstruction (ACLR); these have been shown to be at increased risk of graft rupture. One option that surgeons have pursued to reduce the theoretical failure rate of these smaller-diameter grafts is augmenting them with allograft material, thereby forming a larger-diameter hybrid autograft-allograft construct. Purpose/Hypothesis: The purpose of this study was to compare ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Rao and colleagues 11 in 2020 in another retrospective review of adult and adolescents found augmenting a hamstring autograft that is 8 mm or less with allograft showed no difference in overall reoperation, revision of ACL failure, or patient reported outcomes. Lastly, Heyworth and colleagues 10 in 2021 showed no difference in retear rates and clinical outcomes with augmented grafts in an adolescent group in a retrospective review.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rao and colleagues 11 in 2020 in another retrospective review of adult and adolescents found augmenting a hamstring autograft that is 8 mm or less with allograft showed no difference in overall reoperation, revision of ACL failure, or patient reported outcomes. Lastly, Heyworth and colleagues 10 in 2021 showed no difference in retear rates and clinical outcomes with augmented grafts in an adolescent group in a retrospective review.…”
Section: Discussionmentioning
confidence: 97%
“… 4 Studies assessing the use of allograft augmentation raise concerns for increased rates of graft rupture, particularly in adolescents; however, this is inconclusive in adults. 6 , 7 , 8 , 9 , 10 , 11 The purpose of this study was to assess the discrepancy in graft diameter between double- and quadruple-folded hamstring autografts and the need for allograft augmentation to obtain an adequate graft diameter during ACLR. It was hypothesized that quadruple-folded grafts would have a larger average diameter and reduced need for allograft augmentation.…”
mentioning
confidence: 99%
“…However, due to iatrogenic suboptimal harvest or anatomical variation, the graft can be smaller than preferred [5]. While consensus on the minimum HA graft diameter needed to reduce the risk of graft failure is lacking [8], an inverse association between graft diameter and risk of failure and revision has been reported with most considering a diameter of ≥ 8 mm as the preferred minimum diameter [1, 9, 25]. There are several options for the surgeon when faced with a harvested HA with a diameter < 8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Jacobs et al [10] compared HA (n = 46; average age 14.6) and HY (n = 42; average age 15) and found graft failure was significantly higher for HA (28.3%; mean diameter 7.8 mm) compared to HY (11.9%; mean diameter 9.9 mm) in their retrospective cohort study. More recently, Heyworth et al [8] found no differences between graft re‐tear rates in their retrospective review of HA (n = 64; average age 16.1) and HYs (n = 47, average age 15.8) with a re‐tear rate of 13% for HA (mean diameter 7.1 mm) and 9% for HY (mean diameter 9.1 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Allograft is associated with some negative outcomes, including disease transmission (13), immune rejection (14), and a high risk of surgery failure (14). A hybrid graft combines allograft (tibialis posterior, tibialis anterior, gracilis tendon, or semitendinosus) with auto hamstring tendons to strengthen the autograft, resulting in a graft with a thicker diameter and a larger graft occupancy than that of autograft (15,16).…”
Section: Introductionmentioning
confidence: 99%